Peningkatan Skill Siswa SMK Taruna Surabaya melalui Training Software Kelistrikan Terkini - Projek Priyonggo; Boedi Herijono; Imam Sutrisno; Rini Indarti; Didik Dwi Suharso (Bulletin of Community Engagement, 2024)
Technological developments in the electrical sector are increasingly rapid, demanding competent workers who master the latest software. Taruna Vocational School Surabaya as a vocational high school (SMK) in the field of electricity needs to improve its students' skills so they are ready to compete in the world of work. This research aims to improve the skills of students at Taruna Vocational School in Surabaya through the latest electrical software training. The research method used is a qualitative method with a descriptive approach. Data was collected through observation, interviews and document analysis. The research results show that the latest electrical software training has proven effective in improving the skills of students at Taruna Vocational School in Surabaya. This is proven by the increase in students' practical exam scores and the increase in students' ability to use the latest electrical software. This research makes a contribution to SMK Taruna Surabaya in improving the quality of education and competency of its students. The results of this research can also be a reference for other schools in improving their students' skills through the latest electrical software training.